Die europäischen Limnobaris-Arten (Coleoptera, Curculionidae). - Dieckmann, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1991)
The genus Limnobaris Bedel is represented in Europe by 3 taxa. The name Limnobaris pilistriata (Stephens) is to replace by the older name L. dolorosa (Goeze) and the name L. t-album var. reitteri Munster by the older name L. t-album ssp. atriplicis (F.). L. dolorosa is a distinct species and widely distributed in Europe. L. t-album (L.) and L. t-album ssp. atriplicis (F.) are geographical subspecies with a hybridisation area in the environmental of Leningrad. In all three taxa there are insular local pupulations with a considerable variation. For Curculio dolorusus Goeze, 1777, a neotype is designated. Lectotypes are designated for 6 nominal taxa. Nomenclatural Acts pusio Boheman, 1844 (Baridius), syn. n. of Limnobaris t-album atriplicis (Fabricius, 1792) martulus Sahlberg, 1890 (Baridius (Limnobaris)), Lectotype; syn. n. of Limnobaris t-album (Linnaeus, 1758) pilistriatus Stephens, 1831 (Baris), Lectotype; syn. n. of Limnobaris dolorosa (Goeze, 1777) sculpturata Faust, 1885 (Baris t-album var.), syn. n. of Limnobaris dolorosa (Goeze, 1777) dolorosus Gmelin, 1790 (Curculio), homonym; syn. n. of Limnobaris dolorosa (Goeze, 1777) funereus Geoffroy, 1785 (Curculio), syn. n. of Limnobaris dolorosa (Goeze, 1777) funereus Herbst, 1795 (Curculio), Lectotype; syn. n. of Limnobaris dolorosa (Goetze, 1777) nigrinus Herbst, 1795 (Curculio), Lectotype; syn. n. of Limnobaris t-album atriplicis (Fabricius, 1792) barbiellinii Leoni, 1907 (Limnobaris), syn. n. of Limnobaris dolorosa (Goeze, 1777) dolorosa (Goeze, 1777) (Limnobaris), Neotype described as Curculio dolorosus koltzei Faust, 1891 (Limnobaris), syn. n. of Limnobaris dolorosa (Goeze, 1777) atriplicis (Fabricius, 1792) (Limnobaris t-album), Lectotype hitherto Curculio atriplicis